Efficacy and safety of a personalized vitamin D3 loading dose followed by daily 2000 IU in colorectal cancer patients with vitamin D insufficiency: interim analysis of a randomized controlled trial - Kuznia, Sabine; Czock, David; Kopp-Schneider, Annette; Caspari, Reiner; Fischer, Harald; Laetsch, Dana Clarissa; Slavic, Marija; Brenner, Hermann; Schöttker, Ben (Nutrients, 2022)
A personalized vitamin D3 loading dose has not yet been tested in cancer patients. This interim analysis of the randomized, placebo-controlled VICTORIA trial analyzed the first recruited 74 German adults with nonmetastatic colorectal cancer, a tumor surgery within the past year, and 25-hydroxyvitamin D levels (25(OH)D) < 50 nmol/L.
Gesehen am 31.01.2023